2011
DOI: 10.5021/ad.2011.23.4.474
|View full text |Cite
|
Sign up to set email alerts
|

Narrowband Ultraviolet B Phototherapy of Early Stage Mycosis Fungoides in Korean Patients

Abstract: BackgroundNarrowband UVB (NBUVB) is currently used to treat early mycosis fungoides (MF). There are a number of reports on the efficacy and safety of NBUVB in Caucasians, but little data is available for Asians.ObjectiveThis study was designed to evaluate the effectiveness and safety of NBUVB for early stage MF in Korean patients.MethodsWe enrolled 14 patients (12 men, 2 women; age range, 10~64 years) with clinically and histologically proven MF. Three patients were stage IA, and the others were stage IB. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
13
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
4
13
0
Order By: Relevance
“…The reported rate of complete response to NB-UVB in stage I disease ranged from 50% to 82%. [27][28][29][30][31][32] These rates are similar to the effectiveness of PUVA when assessed in comparable studies. [33][34][35][36] For solitary or discrete lesions, single-dose local radiation is another treatment option, which was recently reported to have an 85% complete response in 58 patients with 270 lesions (94% lesional response rate) at a median follow-up of 41Á3 months.…”
Section: Commentsupporting
confidence: 64%
See 1 more Smart Citation
“…The reported rate of complete response to NB-UVB in stage I disease ranged from 50% to 82%. [27][28][29][30][31][32] These rates are similar to the effectiveness of PUVA when assessed in comparable studies. [33][34][35][36] For solitary or discrete lesions, single-dose local radiation is another treatment option, which was recently reported to have an 85% complete response in 58 patients with 270 lesions (94% lesional response rate) at a median follow-up of 41Á3 months.…”
Section: Commentsupporting
confidence: 64%
“…Based on those reports, the overall response rate (including complete and partial clearance) to NB‐UVB for stage I disease is 83–100%, and 88–90% in stage I–IIA MF, without severe adverse reactions. The reported rate of complete response to NB‐UVB in stage I disease ranged from 50% to 82% . These rates are similar to the effectiveness of PUVA when assessed in comparable studies …”
Section: Commentsupporting
confidence: 58%
“…In a study with 14 patients, complete remission was observed at a rate of 78.6%, and relapse was reported in 54.5% of these patients which is consistent with our study. 17 In another study, recurrence was observed in 3 of 8 patients, and the extent of lesions in one of these patients was associated with relapse. 18 Ponte et al reported a higher rate of relapse (83.3%) than that in our study.…”
Section: Discussionmentioning
confidence: 90%
“…While some authors believe that clinical stage of CTCL is more important than skin phototype in determining the response to NB-UVB, others have doubts about the effectiveness of NB-UVB in dark-skinned patients because of the photoprotective function of melanin [10]. …”
Section: Discussionmentioning
confidence: 99%